Importance of Stress and Temperature-Dependent Permeability of Rocks and its Application in Underground Nuclear Waste Disposal (MIST International Journal of Science and Technology, 2023)
Water flow is an essential factor in the sealability of any underground cavern, including those for nuclear waste disposal, and is significantly affected by the permeability of the rock. The permeability of rocks is affected by various factors, including stress and temperature. The rock stress changes by excavating a cavern, and rock temperature changes by decay heat from nuclear waste, and the temperature change induces thermal stress. Therefore, water flow around such caverns must be evaluated considering the effects of stress and temperature. Numerical analyses of water migration around underground nuclear waste disposal caverns have been carried out. However, studies considering the stress and temperature-dependent permeability may not be published yet. To demonstrate the necessity to consider the stress and temperature-dependency in permeability, equations that represent the postfailure permeability as a function of average effective stress and temperature were proposed. The water inflow was numerically calculated for a simple underground nuclear waste disposal cavern with or without stress and temperature dependency which showed the significance of the dependency. Also, the importance of rock types was demonstrated by considering the three rocks of granite, sandstone, and tuff for a full-scale underground radioactive disposal site for the stress and temperature-dependent permeability. A high sealability could be expected for granite and sandstone but not for the tuff. Introducing the stress and temperature-dependent permeability could contribute to the thoughtful design of an underground repository for radioactive waste disposal considering rock types.MIJST, Vol. 11, June 2023 : 39-49DOI: https://doi.org/10.47981/j.mijst.11(01)2023.413(39-49)